2008
DOI: 10.1161/hypertensionaha.107.100586
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Aryl Hydrocarbon Receptor Induces Hypoxemia, Endothelin-1, and Systemic Hypertension at Modest Altitude

Abstract: Abstract-The aryl hydrocarbon receptor (AHR) is a basic helix-loop-helix Per-Arnt-Sim transcription factor that mediates induction of metabolic enzymes and toxicity of certain environmental pollutants. Although AHR knockout (KO) mice develop cardiac hypertrophy, conflicting reports associate this pathology with hypotension or endothelin (ET)-1-dependent hypertension. Because hypertension occurred at modest altitude, we tested the hypothesis that loss of AHR increases the sensitivity to hypoxia-induced ET-1, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…1F). In agreement with the findings of a previous study, uninfected AhR-KO mice were found to have a slight decrease in hematocrit compared with WT mice (51).…”
Section: Ahr Deficiency Results In Increased Parasitemia and Mortalitsupporting
confidence: 92%
“…1F). In agreement with the findings of a previous study, uninfected AhR-KO mice were found to have a slight decrease in hematocrit compared with WT mice (51).…”
Section: Ahr Deficiency Results In Increased Parasitemia and Mortalitsupporting
confidence: 92%
“…Such a developmental role may be an evolutionarily conserved primary function of the AHR, a notion supported by the finding that unlike their vertebrate counterparts, AHR orthologs in invertebrates like the fruit fly D. melanogaster and the nematode C. elegans are not activated by xenobiotic ligands but control expression of homeotic genes involved in neuronal specification during development (Emmons et al, 1999; Hahn, 2002; Qin and Powell-Coffman, 2004; Kim et al, 2006). In mice, Ahr ablation leads to impaired vasculature in kidney, liver sinusoid, and eyes of the neonates (Lahvis et al, 2000) with an ensuing cardiovascular disease that might be directly or indirectly the principal cause of other Ahr deficit phenotypes, such as reduced liver size, patent ductus venosus , cardiac hypertrophy, hypertension, and fibrosis (Fernandez-Salguero et al, 1995; Fernandez-Salguero et al, 1997; Lund et al, 2003; Lahvis et al, 2005; Lund et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Measurement of Blood Pressure, Heart Rate, and Activity by Radiotelemetry. Mean arterial blood pressure (MAP), heart rate (HR), and activity were measured using radiotelemetry (Data Sciences International, St. Paul, MN) in CYP1A1 WT and KO mice fed an n-3 or n-6 PUFA-enriched diet as previously described elsewhere (n 5 4-6 per genotype/diet) (Lund et al, 2008;Kopf et al, 2010;Agbor et al, 2012). Seven days after surgery, we recorded MAP, HR, and activity for 10 seconds every 15 minutes for 7 days before treatment with LNNA in the drinking water (250 mg/l) for 3 days (Duling et al, 2006).…”
mentioning
confidence: 99%